VUV pressure-broadening in sulfur dioxide. (May 2018) - Lyons, J.R.; Herde, H.; Stark, G.; Blackie, D.S.; Pickering, J.C.; de Oliveira, N.
Highlights: Pressure broadening is measured for SO2 at 215 nm for N2 and CO2 bath gases. Pressure broadening is greater at 215 nm versus 308 nm and 7.4 µm. Pressure broadening explains isotope effects seen in SO2 photolysis experiments. Pressure broadening in SO2 diminished isotope effects in the early Earth atmosphere. Abstract: In the pre-oxygenated ancient Earth atmosphere, the lack of O3 absorption allowed ultraviolet photodissociation of numerous molecules in the troposphere and lower stratosphere. For molecules with narrow line-type absorption spectra, optically thick columns would have produced isotope fractionation due to self-shielding of the most abundant isotopologues. In the lower atmosphere pressure broadening would modify, and in some cases, eliminate these isotope signatures. Shielding is particularly important for quantifying or constraining photolysis-derived isotope effects, such as those believed to explain the sulfur mass-independent fractionation in Archean sedimentary rocks. Here, we report pressure broadening coefficients for natural abundance SO2 in the C ˜ 1 B 2 ← X ˜ 1 A 1 band system at 215 nm. For gas bath pressures up to 750 mbar, we find broadening coefficients of 0.30 ± 0.03 cm − 1 atm −1 and 0.40 ± 0.04 cm − 1 atm −1 for N2 and CO2, respectively. These broadening coefficients are ∼30% larger than SO2 broadening coefficients previously measured in the B ˜ − X ˜ bands at 308 nm. Because of the highly congested nature of the C ˜ − X ˜ bands, pressure broadening in the early Earth troposphere will cause line profile overlap that will diminish the self-shielding-derived mass-independent isotope fractionation for optically thick SO2 columns. Thus, non-explosive volcanic eruptions may not have left a signature of SO2 self-shielding in the ancient sedimentary rock record.